1995
DOI: 10.1002/malq.19950410213
|View full text |Cite
|
Sign up to set email alerts
|

La relation différence et l'anti‐isomorphie

Abstract: This paper deals with pairs of binary relations defined on the same finite basis and which the %element restrictions are isomorphic and those of 5-element restrictions are isomorphic or anti-isomorphic. To each of these pairs, we associate an equivalence relation which yields a decomposition of these relations into classes that we will characterize. As application, we get the treshold of half-reconstruction for tournaments. MathematicsSubject Classification: 03C60, 04A05, 06A05. Le diamant positif, not6 6+, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Concerning the half-reconstructibility problem, Y. Boudabbous and G. Lopez [2] established that the tournaments are ( 7)-half-reconstructible and showed that the value 7 is the best possible. In this Note, we characterize the ( k)-half-reconstructible tournaments for k ∈ {3, 4, 5, 6}.…”
Section: Given a Tournament T = (V A) With Each Non-empty Subsetmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the half-reconstructibility problem, Y. Boudabbous and G. Lopez [2] established that the tournaments are ( 7)-half-reconstructible and showed that the value 7 is the best possible. In this Note, we characterize the ( k)-half-reconstructible tournaments for k ∈ {3, 4, 5, 6}.…”
Section: Given a Tournament T = (V A) With Each Non-empty Subsetmentioning
confidence: 99%
“…Concernant la demi-reconstruction [7], Y. Boudabbous et G. Lopez [2] ont établi la ( 7)-demi-reconstruction des tournois, de plus la valeur 7 est optimale. Dans cette Note, nous caractérisons les tournois ( k)-demi-reconstructibles pour 3 k 6.…”
Section: Proposition 11 Un Tournoi Est ( 3)-reconstructible Si Et Sunclassified
See 1 more Smart Citation
“…Par analogie avec les problèmes de reconstruction dus à Ulam [11] et à Fraïssé [5], Hagendorf [7] a introduit les problèmes de demi-reconstruction. Boudabbous et Lopez [2] ont établi la {1, . .…”
Section: Présentation Des Résultatsunclassified
“…Analogously with the problems of reconstruction ( [5] and [11]), Hagendorf [7] introduced the problems of half-reconstruction. Boudabbous and Lopez [2] established the {1, . .…”
mentioning
confidence: 99%